Planetary and Intericonicity: Diagram of a Collaborative, Digitally-enabled Research Project. Issue 1 (29th December 2014) - Labarre, Nicolas
Abstract : This note presents a diagram of a collaborative project about the comic book series Planetary (1998–2009). It introduces the image by arguing that such a diagram makes it possible to visualize the complexity of relationships between the various academic institutions underpinning the original research project.